Designing English Learning Media for Junior High School Students Using Adobe Flash - Athiyah Salwa; Hafiza Ghassani (University of Surakarta, 2023)
Nowadays, it is important to shape students into autonomous learners since technology and the internet rise massively. Post-pandemic era makes learning English more flexible. It can be done through various kinds of media such as social media, online quizzes and courses, and many applications that support students to be autonomous. Making students to be autonomous learners means they can study with their external motivation by which they can feel motivated and unlimited of time and place. It aims to increase students' motivation and awareness of learning Procedure Text for Junior High School students from an integrated application of material and assessment. The research method was Research and Development, in which the writer will develop software for English teaching media. English teachers can use this application to teach Procedure text because the result shows an improvement in students' achievement and motivation compared to the pre-test conducted before the treatment is given. Product testing on the interface and the material presented in the application showed that students' learning outcomes increased, and satisfaction or interest in English subjects had a significant impact. Both were obtained from the post-test conducted and also observation of the learners.